Eletro narcose como método de insensibilização para a tilápia do Nilo - Bordignon, Adriana Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Animal welfare in aquaculture is attracting great interest, because of the use of handling techniques that cause stress to the animals before death. The objective of this study was to evaluate different methods of stunning/killing in Nile tilapia (Oreochromis niloticus) using electronarcosis, thermal shock and the anesthetic as control, and to evaluate the changes in the quality of chilled fish and frozen fillets. In the first stage, the electronarcosis stunning was applied using different voltages (200V and 100V) and exposure times (20s, 40s, 60s) to find what would be the best combination of voltage and exposure time. Most of the fish remained stunned with the treatments 100V/60s and 200V/60s. The clinical reflexes were absent in fish of treatments 100V/60s, 200V/40s and 200V/60s. Treatment 100V/60s ensured welfare conditions in the stunning and less hemorrhagic fillets. The second experiment included three methods of stunning/killing: 1) electronarcosis (100V / 60s), 2) thermal shock (water and ice) and 3) anesthetic (benzocaine). It was investigated some parameters of freshness of fish cooled at 4 °C and stored for 25 days. The analyzes were performed at 0; 0.13; 0.21; 1; 7; 14; 18; 22 and 25 days. The fishes of the three stunning/killing methods tested, entered in the state of rigor mortis after 7 days of storage, with concomitant reductions in muscle and ocular pH, and ATP levels. Parameters such as dielectric measurement, instrumental texture, content of VNB and NPN presented reductions over the storage time. The K value and the sensory analysis of fish showed that chilled tilapia presented within 7 days of storage, good state of freshness. Microbiological analysis confirmed that the slaughter and processing were performed hygienically. In the third experiment, three methods of stunning were tested in tilapia: 1) electronarcosis (100V / 60s), 2) thermal shock (water and ice) and 3) benzocaine, followed by filleting and the ...

Questões que envolvem o bem estar dos animais na aquicultura vem despertando grande interesse, devido à utilização de técnicas de manipulação que causam estresse aos animais antes da sua morte. O objetivo deste estudo foi avaliar diferentes métodos de insensibilização em tilápia do Nilo (Oreochromis niloticus) utilizando a eletronarcose, choque térmico e anestésico como controle, e avaliar os efeitos sobre alterações na qualidade da carne resfriada e congelada. Na primeira etapa a insensibilização foi realizada por eletronarcose, utilizando diferentes voltagens (200V e 100V) e tempos de exposição (20s, 40s, 60s) para verificar qual seria a melhor combinação de voltagem e tempo de exposição. A maioria dos peixes permaneceu insensibilizada com os tratamentos 100V/60s e 200V/60s. Os reflexos clínicos mostraram-se ausentes nos peixes submetidos aos tratamentos 100V/60s, 200V/40s e 200V/60s. O tratamento 100V/60s garantiu condições de bem-estar na insensibilização dos peixes e filés menos hemorrágicos. No segundo experimento, foram testados 3 métodos de insensibilização: 1) eletronarcose (100V/60s), 2) choque térmico (água e gelo) e 3) anestésico (benzocaína). Investigou-se alguns parâmetros de frescor do pescado resfriado a 4°C e estocado por 25 dias. As análises foram realizadas nos tempos amostrais 0; 0,13; 0,21; 1; 7; 14; 18; 22 e 25 dias. Os peixes do três métodos de insensibilização testados, apresentaram entrada no estado de rigor mortis aos 7 dias de estocagem, concomitante com reduções dos valores de pH muscular, pH ocular e dos níveis de ATP. Parâmetros como medida dielétrica, textura instrumental, o conteúdo de BNV e NNP apresentaram reduções de seus valores ao longo do tempo de estocagem. O valor K e a análise sensorial dos peixes demonstraram que a tilápia refrigerada apresentou em até 7 dias de armazenamento, bom estado de frescor. A análise microbiológica confirmou que o...
Keywords: Peixe; Saude animal; Pescados; Alimentos - Conservação; Avaliação sensorial; Fishes